Speech and action in the Antiquitates Romanae of Dionysius of Halicarnassus: the question of historical change - Hogg, D; Daniel Hogg (2008)
This thesis examines the relationship between speech and action in Dionysius' Antiquitates Romanae. It consists of five main chapters, an introduction and a conclusion. In the introduction I establish the status quaestionis and consider different modes of presenting discourse. Chapter 2 is an intertextual analysis of Dionysius' first preface, AR I.1-8, exploring Dionysius' engagement with his Greek and Roman predecessors. I take one modern theory, concerning Dionysius apparent 'idealisation' of the Roman past, in order to examine the relationship between the Antiquities and Dionysius' rhetorical works. In the four chapters that follow, I trace the changing texture of narrative across the Antiquities, sinking shafts at moments to examine closely what is going on. First (ch. 3), I analyse speech in the Regal Period, focusing on the story of Lucretia and Brutus (AR IV.64-85), and the way that Herodotean allusion meshes with intratextual devices to narrate the fluctuations of the Regal Period. Chapter 4 is a paired reading of (4a) the story of Coriolanus' trial (VII.21-66) and (4b) the story of Coriolanus' encounter with his mother (VII.39-62). Ch. 4a concentrates on Thucydides and Isocrates, and how Coriolanus' trial binds the Greek literary past to the first-century Roman present. In 4b, I examine how Dionysius manages the shift between high politics and family relationships. Chapter 5, on the decemvirate (X.50-XI.44), explores again Roman tyranny, this time in a Republican frame; the power of the senate is consequently in point here. Chapter 6, on AR XIV-XX, probes the questions of Greek and Roman ethnicity and the individual which had arisen in the earlier chapters. In the conclusion I consider the precise question of Dionysius' Augustanism, relating it to Dionysius' apparent status in Rome.